P064 The role of the vagal innervation in a DSS-induced colitis mouse model. (25th January 2019) - Lo Sasso, G; Phillips, B; Foong, C; Talikka, M; Sewer, A; Kondylis, A; Ivanov, N V; Hoeng, J
Abstract: Background: Environmental factors have been identified that affect the course of Crohn's disease (CD) and ulcerative colitis (UC); one of the most relevant is cigarette smoke (CS) and its main active constituent, nicotine. CS has been shown to have a negative effect on the clinical progression of CD and to increase the risk of onset while showing a favourable effect on reducing the disease progression, severity, and occurrence of UC. Both smoking and nicotine are considered as immunosuppressive and alter a wide range of immunologic functions, including innate and adaptive responses. Nicotine can also influence the immune system through its actions on the central nervous system via the activation of the autonomic nervous system, which connects the brain directly to visceral target tissue, through sympathetic and parasympathetic innervations. The parasympathetic nervous system, primarily the vagus nerve, it is one of the endogenous mechanisms that help to regulate the innate immune response, and activation of this response attenuates systemic inflammation, such as in UC and CD. The existence of counterinflammatory vagal-dependent mechanisms has been assessed in colitis mouse models with conflicting results, and the molecular mechanism by which this therapeutic intervention can have an immune-regulatory effect in UC remains unclear. Methods: In order to understand the possible role of the vagus nerve in the CS-dependent attenuation of colitis symptoms in a dextran sulphate sodium (DSS) mouse model, mice were exposed to CS corresponding to 3 concentrations of nicotine (24, 32, and 40 µg/l) for a total of 4 weeks. DSS was provided in drinking water followed by a seven-day recovery period before necropsy. Finally, animals exposed to the medium nicotine concentration (32 µg/l) and the sham control groups were subject to vagal denervation 2 weeks prior CS exposure. Results: Using an omics approach (transcriptomics) together with classical endpoint analysis, we showed that the nicotine dose-dependent effect on the development of mouse UC is not influenced by the vagus nerve. Accordingly, several inflammatory pathway signalling, such as toll-like receptors, interferon γ, nuclear factor kappa B, and signal transducer and activator of transcription, were down-regulated in CS-exposed mice in a nicotine dose-dependent manner but independently of vagal integrity. Conclusions: The current study allows investigation of possible new molecular mechanisms responsible for the attenuation of DSS-induced mouse colitis by CS constituents, such as nicotine. Moreover, these findings indicate that although vagal integrity is important, other counterinflammatory mechanisms come into play if vagal integrity is compromised.